PENCEGAHAN TINDAK PIDANA PENCURIAN MELALUI PEMBINAAN DAN KONSELING PSIKOLOGI DI DESA PATUMBAK I KECAMATAN PATUMBAK - Maswandi Maswandi; Nanang Tomi Sitorus; Khairuddin Khairuddin; Raja Dewan Sanjaya; Najwa Aliya (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
Community Service in Patumbak-I Village, Patumbak District is a village located in Deli Serdang Regency which is not far from Medan City with a distance of 21.8 km for 47 minutes. Community Service is a follow-up to the collaboration that has been carried out between Medan Area University and the Patumbak-I Village Government. This activity was carried out by conducting legal socialization with the theme "Prevention of Criminal Acts of Theft Through Psychological Guidance and Counseling in Patumbak I Village, Patumbak District". This theme is a very important issue to be conveyed and known so that the public knows the legal consequences of criminal acts of theft. The community service team carried out this service as a form of concern for the Patumbak-I village community by holding discussions on the theme of the service and the community service team did not give limits to participants to ask questions with problems of Criminal Acts of Theft. This service began on July 16-18, 2025 by meeting directly with the participants by carrying out the stages, namely preparation, implementation, and results. The results of the implementation of the activity were evaluated by the community service team regarding public knowledge of the crime of theft after the community service team socialized it so that the information conveyed to the community could be accepted as a whole. The problem experienced by the community was that the Supreme Court Regulation Number 2 of 2012 concerning the Settlement of Limitations of Minor Crimes (Tipiring) and the Amount of Fines in the Criminal Code which provided legal uncertainty to perpetrators of the crime of theft, where the community assumed that the perpetrators were released because the nominal value of the stolen goods was below 2.5 million and were not detained, so the Community Service team conveyed the solutions provided.